Implementation of Human Computer Interaction in Education through Sytematic Literature Review and Bibliometric Analysis: A Study On Scopus Database - Rafly Saputra; Nugraha, Jaka; -Ullah, Attia Aman (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue: Human computer interaction in everyday is an interesting thing, so it is necessary to explore the implementation of Human Computer Interaction in education. Purpose: Sytematic Literature Review and Bibliometric Analysis research has not examined Human Computer Interaction in education. Novelty: In addition, Bibliometric mapping based on Co-Authorship is obtained which provides an overview of interconnected authors and authors who have the most citations on the topic Research Methods: This Sytematic Literature Review research uses Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) and Bibliometric Analysis using Biblioshiny and VOSviewer. Results: Bibliometric mapping based on Co-Occurrence obtained an overview of the most frequently used keywords, namely Human Computer Interaction Research Contributions: The study provides actionable insights for educators, instructional designers, developers, and policymakers